2008
DOI: 10.1002/anie.200703514
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Rare‐Earth‐Metal Half‐Sandwich Complexes for the Living trans‐1,4‐Isoprene Polymerization

Abstract: Dedicated to Professor William J. Evans on the occasion of his 60th birthday Nature provides mankind with highly stereoregular polyterpenes, i.e., polymers of isoprene, featuring distinct properties.[1] Natural rubber (NR, caoutchouc or cis-1,4-polyisoprene, cPIP; > 99 % cis content, M n % 2 10 6 g mol À1 ) is the most important polymer produced by plants and is the raw material for numerous rubber applications. Taking into account new developments in synthetic polymer chemistry, a mechanism for living carboca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 183 publications
(110 citation statements)
references
References 44 publications
7
103
0
Order By: Relevance
“…Comparing the performance of 1 with its [AlMe 4 ] analogue [(Tp t Bu,Me )Lu(Me)(AlMe 4 )] ( I Lu ), (Table , runs 10 and 11) revealed that I Lu is only active, when activated by a Brønsted acid, that is, cocatalyst B under the given conditions. Binary system I Lu / B produced polymers with higher trans contents compared to the boryl‐implemented system 1 / B , which is in analogy the polymers fabricated by similar Cp*‐supported systems , . Furthermore, complex [Cp*Lu(AlMe 3 {B(NDippCH) 2 }) 2 ] ( II ) has been investigated previously by us (Table , runs 12–17) .…”
Section: Resultsmentioning
confidence: 54%
“…Comparing the performance of 1 with its [AlMe 4 ] analogue [(Tp t Bu,Me )Lu(Me)(AlMe 4 )] ( I Lu ), (Table , runs 10 and 11) revealed that I Lu is only active, when activated by a Brønsted acid, that is, cocatalyst B under the given conditions. Binary system I Lu / B produced polymers with higher trans contents compared to the boryl‐implemented system 1 / B , which is in analogy the polymers fabricated by similar Cp*‐supported systems , . Furthermore, complex [Cp*Lu(AlMe 3 {B(NDippCH) 2 }) 2 ] ( II ) has been investigated previously by us (Table , runs 12–17) .…”
Section: Resultsmentioning
confidence: 54%
“…As a clear identification of the active species was not successful so far, due to the paramagnetic character of most of the lanthanide ions and the low tendency of the active species toward crystallization, active species elucidation remains challenging. A reasonable interpretation of this polymerization behavior seems to be that solvent [4,5,13,37], pre-reaction side products (e.g., Ph 3 CMe (A) and PhNMe 2 (B): Ln(III)-arene coordination) [38][39][40], or even anion coordination (e.g., via Ln(III)-F interactions) [41] come into play. Furthermore, dimerization might take place or a η 2 -to-η 3 coordination switch of the remaining tetramethylaluminate moiety, which tendency seems more pronounced for the larger lanthanides as found for the neutral precatalysts [4,10,12].…”
Section: Polymers Obtained At Standard Conditionsmentioning
confidence: 99%
“…Thed imeric 4,4'-bipyridine complex 3d is dark-red colored and is one of only few yttriumbipyridine complexes reported to date and the first with flanking organometallic moieties. [13] In complex 4,the aluminum atom is markedly bent out of the C1-C2-C4-C5-plane (0.824 )due to the steric demand of the C 6 F 5 ligands.Asaresult, the Y···Al distance of 3.071 (2) is much larger than that in the parent complex 1-Y.T he C À C distances within the aluminabenzene ring, however,d on ot deviate remarkably from those in 1-Y.T he Y···F distance (2.413(9) )lies in between literature-known Y···F distances for bridging (2.217(5) ) [14] and weakly coordinating (2.786-(2) ) [15] fluorine atoms.A si ndicated by av ariable-temperature 19 FNMR experiment, an Y···F interaction seems to emerge in solution at lower temperatures ( Figure S29), since signals assigned to the bridging C 6 F 5 ligand started to broaden considerably at temperatures below À40 8 8C. 1 HNMR spectroscopy revealed that the aluminabenzene and 2,4-ditert-butylpentadienyl ligands remained intact showing only slightly shifted proton signals,i na ddition to the CH 3 /C 6 F 5 exchange.T his was also confirmed by XRD measurements, along with the routine U-conformation of the pentadienyl ligand.…”
mentioning
confidence: 99%